Simulation and Analysis of Changes in Carbon Storage and Ecosystem Services Against the Backdrop of Land Transfer: A Case Study in Lvzenong Park - Nan Chen; Wanqing Nie; Weiguo Fan (Land)
Land transfer is a key issue affecting ecosystem services and carbon storage. Land use change can promote or inhibit carbon emission. To study these impacts, a carbon flow model for Lvzenong Park, Yi County, Taihang Mountains, China, was developed using Odum’s energy systems language. The model simulates carbon flow and storage changes from 2015 to 2115 and analyzes changes in ecosystem service values using the equivalent factor method. Finally, two scenarios of economic development and carbon sink protection are set, and the evolution characteristics of carbon storage and ecosystem service under different scenarios are discussed. The key findings include the following: (1) From 2015 to 2115, carbon storage in apple orchards, forests, and grassland systems initially increase then decrease, while soil carbon storage declines steadily and the overall atmospheric CO2 carbon pool increases. Ecosystem service value decreases by 71.30%. (2) Economic development positively affects apple orchards and atmospheric CO2 carbon storage but negatively impacts grassland carbon storage. Conversely, carbon sink protection benefits grassland and soil carbon storage but harms the atmospheric CO2 carbon pool. (3) Under economic development, ecosystem service values initially increase then decline, while under carbon sink protection, they generally rise. These findings provide scientific guidance for formulating land transfer policies and promoting low-carbon development in mountainous regions.